Design, synthesis and biological evaluation of 4-aniline-thieno[2, 3-d]pyrimidine derivatives as MNK1 inhibitors against renal cell carcinoma and nasopharyngeal carcinoma. Issue 11 (1st June 2019) - Zhang, Min; Jiang, Li; Tao, Jia; Pan, Zhaoping; He, Mingyao; Su, Dongyuan; He, Gu; Jiang, Qinglin
Graphical abstract: Abstract: MAP Kinase Interacting Serine/Threonine Kinase 1 (MNK1) play important roles in the signaling transduction of MAPK pathways. It is significantly overexpressed in renal clear cell carcinoma and head-neck squamous cell carcinoma tissues in both mRNA and protein levels. Based on the crystallographic structure of MNK1 protein and binding modes analysis of known MNK inhibitors, we have designed and synthesized a series of 4-aniline-thieno[2, 3- d ]pyrimidine derivatives as potential MNK1 inhibitors. These synthetic compounds are tested in biochemical and cell proliferation assays, and six of them display potent inhibitory capacity against MNK1 kinase and cancer cell lines. Compound12dj with strongest inhibitory capacity is transferred to molecular mechanism studies, and the results indicated that12dj remarkably suppresses the phosphorylation of EIF4E, a substrate of MNK1. And the expression levels of MNK1, ERK1/2 and pERK1/2 are not affected by compound12dj incubation in SUNE-1 and 786-O cells. In summary, our works suggested that these novel 4-aniline-thieno[2, 3- d ]pyrimidine based MNK1 inhibitors might be attractive lead compounds for targeted therapy of renal cell carcinoma and nasopharyngeal carcinoma.